Advances in Biometrics for Secure Human Authentication and Recognition - Kisku, Dakshina Ranjan; Gupta, Phalguni; Sing, Jamuna Kanta (CRC Press, 2013)
This book showcases the technologies and algorithms being used for human authentication and recognition. Examining the full range of biometrics solutions, including unimodal and multimodal biometrics, the book covers conventional biometric techniques as well as novel systems developed over the past few years.